An Analysis Of Geogebra Method For Visual Design PID Control System - Nimas Deria Wijayanti; Parlin Siagian; Zuraidah Tharo (Sean Institute, 2024)
The design of Proportional-Integral-Derivative (PID) control systems is a critical aspect of control engineering to achieve system stability and optimal performance. How-ever, tuning PID parameters often poses challenges due to the complex analytical ap-proaches required. This study analyzes the application of GeoGebra, a dynamic mathe-matics software, in designing PID control systems visually. GeoGebra is utilized to model control systems, visualize system responses, and perform interactive PID parameter tun-ing. The study involves simulations of simple linear systems, such as actuator position control, to evaluate the effectiveness of the GeoGebra method compared to traditional approaches. The analysis focuses on performance parameters, including rise time, peak time, and steady-state error. The results demonstrate that GeoGebra simplifies the PID parameter tuning process through intuitive visualization, enhancing concept comprehen-sion and design efficiency. Furthermore, GeoGebra proves to be an effective tool for edu-cation and training in control engineering.